2006
DOI: 10.1177/1748895806068572
|View full text |Cite
|
Sign up to set email alerts
|

The impact of work–family conflict on correctional staff

Abstract: Work–family conflict (WFC) occurs when the work domain and family domain are incompatible with one another in some manner. A survey of staff at a private Midwestern prison measured four dimensions of WFC: time-based work on family conflict, strain-based work on family conflict, behavior-based WFC and family on work conflict. Ordinary Least Squares (OLS) regression results indicate that strain-based conflict was the only form of WFC to have a significant effect on job stress. Both strain-based conflict and beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
147
3
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(159 citation statements)
references
References 28 publications
7
147
3
2
Order By: Relevance
“…Given the regimented, almost militaristic, tendency of work inside the prison walls, incongruence and conflicts between work and family domains may be more frequent or magnified for correctional employees. Indeed, prior studies have found a number of work-family conflict dimensions to be linked to job stress and job satisfaction (Lambert et al, 2006) as well as eventual job burnout .…”
Section: Work-family Conflictmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the regimented, almost militaristic, tendency of work inside the prison walls, incongruence and conflicts between work and family domains may be more frequent or magnified for correctional employees. Indeed, prior studies have found a number of work-family conflict dimensions to be linked to job stress and job satisfaction (Lambert et al, 2006) as well as eventual job burnout .…”
Section: Work-family Conflictmentioning
confidence: 99%
“…Lambert et al (2006) defined time-based conflict as work demands that result in home conflict because the officer is spending insufficient time tending to family needs. For example, due to organizational turnover and a lack of qualified job applicants, it is not unusual for correctional officers to work overtime or pick up extra shifts.…”
Section: Work-family Conflictmentioning
confidence: 99%
See 2 more Smart Citations
“…The most studied construct in work-family literature, arises when an individual is faced conflicts and simultaneous demands that stem from either his work or family role [9,14]. Many prominent researchers have linked work-family conflict with numerous problems: domestic violence [15], poor physical activity [16], poor eating habits [17], poor emotional health [18], excessive drinking [16], substance abuse [19], decreased marital satisfaction [20], decreased emotional wellbeing [21], and neuroticism [22]. As mentioned earlier, workfamily conflict, as an inter-role conflict in which work and family demands are mutually incompatible [13], can create stress, which is basically a form of unpleasant emotion [23].…”
Section: Introductionmentioning
confidence: 99%